Analysis of Mathematical Spatial Abilities of Vocational School Students In Solving Transformation Geometry Problems - Yusuf, Yusfita; Nabila, Intan (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2024)
Geometry is one of the branches of mathematics that is important for students to master to support their profession in the future. However, there are still difficulties in geometry materials, especially transpormation geometry. In fact, there are many test questions about transformation geometry when taking the university or job entrance test. Therefore, it is necessary to conduct an analysis of spatial ability in solving the transformation geometry problem. This study uses a descriptive qualitative approach involving 24 grade XII students in Sumedang Regency as subjects. The results showed that students with high spatial abilities were able to visualize transformations well, although they still faced difficulties in translating them into proper mathematical models. In contrast, students with moderate and low spatial abilities showed significant challenges in understanding the basic concepts of geometric transformations. This study underlines the importance of applying spatial-based learning strategies to improve students' competence in understanding and applying geometry concepts effectively.